Empirical Analysis of Renewable Energy Consumption, Environmental Pollution and Official Development Assistance Impact on Human Development: Evidence from OECD Countries - Tatli, Halim (International Journal of Economics, Management and Accounting, 2022)
This study is aimed at establishing some of the key factors that have affected Human Development from 1990 to 2017. The Human Development Index was used as a dependent variable while renewable energy consumption, total CO2 emission, official development assistance, mean years of schooling, life expectancy at birth, employment to population ratio and population were used as the independent variables. Panel Data Analysis and panel causality were used to analyze the data. The conclusions show that renewable energy consumption, CO2, official development assistance, mean years of schooling, life expectancy at birth, and employment to population ratio affect the Human Development Index positively, while population affects the HDI negatively. Also, there is a bidirectional causality running from renewable energy consumption to HDI, from official development assistance, to HDI, from mean years of schooling to HDI and from employment to population ratio to HDI for the whole panel. Therefore, it was established that all independent variables in the study model are among the key determinants of human development.